When Checking a Box is not Enough: The (Un)Readability of PREA Messaging - Krienert, Jessie L. (The prison journal, 2023)
The Prison Rape Elimination Act (PREA) was implemented to prevent sexual assault within correctional facilities. To communicate PREA principles to inmates, written materials including handbooks, policies, and brochures are utilized. This research evaluates the readability of PREA messaging, employing three established metrics: Flesh Reading Ease Score, Flesch–Kincaid Grade Level, and Simple Measure of Gobbledygook. Findings reveal significant deviation from recommended reading targets for both the general (7th–8th grade) and inmate (5th–6th grade) populations. Prison Rape Elimination Act policies averaged a 16th-grade level, raising concerns regarding the efficacy of PREA implementation and compliance in light of potential comprehension challenges.